(3QjMGf GdeQhL hOjHGL GdacQ GdefShL GdcGTa eG GOdge ef GdSjQI GdeUWahjIs - (3ESeGYjd Hf EHQGgje Hf YWjg GdfLQGfj,J (B794 (3g` s ((3Ydi Hf CMeO Hf MSf Hf QGTO GdTYTGY s)
(3ChdgG (B:s
(3HYO GdHSedI (B: (3PcQ eDda cJGH SjQI QShd Gddg Ydjg hSde gh hCHh HcQ eMeO Hf ESMGb Hf jSGQ GdeWdHj s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B307 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B175 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs